Rehabilitation of ankle and foot injuries in athletes - Chinn, L.; Hertel, J. (Clinics in Sports Medicine, 2010)
Foot and ankle injuries are extremely common among athletes and other physically active individuals. Rehabilitation programs that emphasize the use of therapeutic exercise to restore joint range of motion, muscle strength, neuromuscular coordination, and gait mechanics have been shown to have clinical success for patients suffering various foot and ankle pathologies. Rehabilitation programs are discussed for ankle sprains, plantar fasciitis, Achilles tendonitis, and turf toe.